Towards Real-Time Oxygen Sensing: From Nanomaterials to Plasma - Johny, Vinitha; Chinmaya, K. V.; Nihal C. V., Muhammed; Kurian, Varghese; Rao, G. Mohan; Ghosh, Moumita; Ghosh, Siddharth (Frontiers in Sensors, 2022)
A significantly large scope is available for the scientific and engineering developments of high-throughput ultra-high sensitive oxygen sensors. We give a perspective of oxygen sensing for two physical states of matters—solid-state nanomaterials and plasma. From single-molecule experiments to material selection, we reviewed various aspects of sensing, such as capacitance, photophysics, electron mobility, response time, and a yearly progress. Towards miniaturization, we have highlighted the benefit of lab-on-chip-based devices and showed exemplary measurements of fast real-time oxygen sensing. From the physical–chemistry perspective, plasma holds a strong potential in the application of oxygen sensing. We investigated the current state-of-the-art of electron density, temperature, and design issues of plasma systems. We also show numerical aspects of a low-cost approach towards developing plasma-based oxygen sensor from household candle flame. In this perspective, we give an opinion about a diverse range of scientific insight together, identify the short comings, and open the path for new physical–chemistry device developments of oxygen sensor along with providing a guideline for innovators in oxygen sensing.